Comparison of Waste Disclosure Based on GRI Standards in Subsidiary Companies of Pupuk Indonesia - Gale Faustina (Universitas Kristen Maranatha, 2023)
In today’s world there has been an increase of expansions and developments of importance in industrial estates. The direct impact which has occurred from the expansion of the Industry is caused by pollution which occurred in the surrounding environment. The fertilizer industry is one of the industrial sectors which produces toxic and hazardous by-products that is harmful to the environment. PT. Pupuk Indonesia Holding Company (Persero) is one of the largest fertilizer producers in Asia and the top ten in the world. It is necessary to apply appropriate standards and according to the needs of each company. The GRI standards are standards that are widely used in terms of reporting economic, environmental and social impacts to the public. One of the indicators discussed in the GRI Standards is related to waste. This study aims to evaluate the comparison of disclosure of waste in sustainability reports based on the GRI standards at Pupuk Indonesia Group's subsidiaries. The results of the study show that all companies have indicators related to waste, and there is not a single company that does not disclose GRI indicators related to waste. PT. Pupuk Kalimantan Timur is the best, while PT. Pupuk Kujang is at the bottom. Keywords: Fertilizer Company, GRI Standards, Sustainability Report, and Waste